An Efficient online blood bank service using cloud based database system - T., Abinesh; Saravanan., M.S (International Journal of Psychosocial Rehabilitation, 2020)
1 in 7 people entering a hospital need blood. For every 2 seconds, someone is in need of blood. Health care services are very essential and are basically important as well. With the usage of technology and the latest methodology, these services can be delivered in a better manner. A lot of things change with the advancement of medical science; many synthetic substitutes are used, but there are no substitutes for human blood. The collected blood has a shelf life of 42 days, and so blood that is available in an emergency situation is considered precious. Fast communication can be very useful in medical emergencies. Consider having a faster and updated data flow in any e-service related to health care, which will surely boost the communication of data and can possibly save human lives. Having technologies like cloud computing at your disposal can be very efficient when coupled with real-time databases.